O niektórych możliwościach wykorzystania mandali w edukacji polonistycznej - Krzyżyk, Danuta (Postscriptum Polonistyczne, 2020)
The article presents the possibility of using mandala during the classes with children studying Polish as a foreign language. Some particular areas of Polonistic education have been discussed here, such areas where using this technique supporting passing the knowledge and developing skills is possible. The functions of educational mandala have been described along with the most important rules of using it. Working with the picture of mandala can help to liberate a child’s creative activity.